Norwegian Oil Experience and The Possibility of Benefiting From it in Iraq - Idrees Sulaiman Abdullah (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
It is obvious that the oil sector in Iraq is suffering from major problems related to oil infrastructure, in terms of extraction, production, transport, storage and export outlets. Generally, it is often said that the economic policy including the oil policy, have been failed in setting the short- and long-term plans to manage and best use the oil wealth. Although there are a number of official institutions to manage oil industry in Iraq, there is no competent authority in the area of investment and management of surplus reserves which is deposited in a development fund of Iraq (DFI). It is emphasized that Iraq’s need to invest these reserves, despite the existence of some intersections between the monetary policy and the fiscal policy. Yet, oil revenues, constitute more than 90% of the public budget of the country. On the other hand, the Norway experience has become a successful model in the oil industry among oil export countries, includes the level of extraction, manufacture and export of oil derivatives. it is possible to benefit from its experience in this sector through attempting to apply its oil investment policy and to be guided in all phases of the oil industry. As a result of its remarkable success is achieved in the oil sector, the researcher will study all development stages and the reasons for the success regarding the oil industry in Norway, particularly in term of establishing sovereign wealth funds (SWFs) and its role in economic and financial stability